2002
DOI: 10.1364/josab.19.000289
|View full text |Cite
|
Sign up to set email alerts
|

Limits to the determination of the nonlinear refractive index by the Z-scan method

Abstract: We analyze the limitations imposed by sample absorption on the determination of the nonlinear refractive index by the Z-scan technique. By using a nanostructured thin film consisting of Cu nanocrystals embedded in a dielectric Al 2 O 3 matrix as an example, we show that thermo-optical effects appearing when linear absorption is significant can be strongly misleading in the interpretation of the results of a Z scan. Even though this effect is not new, the widespread use of the Z-scan technique during the past s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 48 publications
0
48
1
Order By: Relevance
“…Narrow pulse width and low repetition rate, combined with sufficiently low input peak irradiance, are ideal parameters for avoiding such risks. [22] In THG, once the sample is irradiated with a monochromatic optical beam at frequency w, a beam at frequency 3 w and one at frequency w, both dependent on the third-order polarization, are generated. These two signals interfere inside the material to produce the so-called Maker fringes when the sample is rotated.…”
Section: Experimental Techniques: a Comparisonmentioning
confidence: 99%
“…Narrow pulse width and low repetition rate, combined with sufficiently low input peak irradiance, are ideal parameters for avoiding such risks. [22] In THG, once the sample is irradiated with a monochromatic optical beam at frequency w, a beam at frequency 3 w and one at frequency w, both dependent on the third-order polarization, are generated. These two signals interfere inside the material to produce the so-called Maker fringes when the sample is rotated.…”
Section: Experimental Techniques: a Comparisonmentioning
confidence: 99%
“…Due to these thermal effects, the sample behaves as an optical lens, which might lead to an overestimation of nonlinear parameters obtained by the Z-scan method. With our measurements conditions and considering a thermal diffusion coefficient of D ~ 0.55 cm 2 /s for InN [16] these thermal effects could affect to the measurements for laser repetition rates above ~1 MHz [17]. However, it must be pointed out that the obtained nonlinear absorption corresponds to the expected behavior of the analyzed samples in a telecommunication application under high repetition rates.…”
mentioning
confidence: 99%
“…Liao et al have also invoked thermal effects to explain the discrepancies observed between different pulse temporal regimes [103]. Furthermore, several authors have demonstrated the involvement of thermal lens in the value of (3) χ , stemming from cumulative thermal effects generated at high pulse repetition rates [104][105][106][107]. We are thus led to define the thermo-optical contribution to the nonlinear refraction and absorption coefficients, th γ and th β .…”
Section: Application To the Nonlinear Response: Thermal Lens Contribumentioning
confidence: 99%